Radiodense dural sinuses: new CT sign in patients at risk for hypoxemic insult. - Nelson, M D; Thompson, J R; Hinshaw, D B; Hasso, A N (American Journal of Neuroradiology, 1981)
The observation of apparent dural sinus opacification in a polycythemic patient with cerebral infarction prompted a review of 300 computed tomographic scans for the significance of dense dural sinuses. Fifteen patients including 11 neonates, were identified; each of them had dense dural sinuses and elevated hematocrit or red blood cell indices or both. With only one exception, computed tomography also showed various low attenuation parenchymal abnormalities. A typical cerebral infarction pattern was seen in six and parenchymal hemorrhage in one. Nonthrombotic dural sinus opacification is a sign of increased blood viscosity in patients with congenital heart disease, hemoconcentration states, polycythemia of the newborn, and polycythemia rubra vera. These patients are at high risk for hypoxemic cerebral insult, which can be detected by cranial computed tomography.